Economic evaluation of culprit lesion only PCI vs. immediate multivessel PCI in acute myocardial infarction complicated by cardiogenic shock: the CULPRIT‑SHOCK trial - Robles‑Zurita, Jose Antonio; Briggs, Andrew; Rana, Dikshyanta; Quayyum, Zahidul; Oldroyd, Keith G.; Zeymer, Uwe; Desch, Stefen; de Waha‑Thiele, Suzanne; Thiele, Holger (Springer Link, 2022)
This article was published in The European Journal of Health Economics by Springer Link [Copyright © 2020, The Author(s)] and the definite version is available at: https://doi.org/10.1007/s10198-020-01235-3 The Journal's website is at: https://link.springer.com/article/10.1007/s10198-020-01235-3#citeas